THE EFFECT OF PROBLEM BASED LEARNING MODEL ASSISTED CONCEPT MAP TO AUTHENTIC PROBLEM SOLVING SKILLS TOPIC ON DYNAMIC ELECTRIC GRADE X SMA NEGERI 1 SIDIKALANG A.Y 2015/2016 - Harahap, Mara Bangun; Silalahi, Novita Sari (JURNAL IKATAN ALUMNI FISIKA, 2016)
The purpose of this study was to determine the effect of problem based learning model to authentic problem solving skills of students topic on dynamic electric grade XÂ  SMA Negeri 1 Sidikalang . This type of research is quasi-experimental. The population of this entire class X SMA Negeri 1 Sidikalang consist of 11 classes. The sample in this study was taken by a random sampling of two classes thatâs X-8 class asexperiment class with 23 students and X-7 class as control class with 26 students. The instrument usedÂ  to determine student learning outcomes in the material dynamic electric in the form of essay test with numbered 10 and observation sheet. The results obtained by testing hypotheses is concluded that there is a significant relationship between use problem based learning model to authentic problem solving skills of students grde X SMA Negeri 1 Sidikalang.